2016
DOI: 10.18632/oncotarget.12184
|View full text |Cite
|
Sign up to set email alerts
|

Successful TB treatment induces B-cells expressing FASL and IL5RA mRNA

Abstract: Activated B-cells increase T-cell behaviour during autoimmune disease and other infections by means of cytokine production and antigen-presentation. Functional studies in experimental autoimmune encephalomyelitis (EAE) indicate that B-cell deficiencies, and a lack of IL10 and IL35 leads to a poor prognosis. We hypothesised that B-cells play a role during tuberculosis. We evaluated B-cell mRNA expression using real-time PCR from healthy community controls, individuals with other lung diseases and newly diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…The results indicated that there is an increase in the levels of both genes by month 6 of treatment. In a previous study, we found that the levels of FasL and Il5Ra of the untreated TB cases were lower when we compared it to that of community controls (data not shown) . These results correlate with the phenotypic results which indicates that there is an increase in the surface expression of FASL and IL5RA during treatment, even though those changes are not statistically significant.…”
Section: Discussionsupporting
confidence: 59%
“…The results indicated that there is an increase in the levels of both genes by month 6 of treatment. In a previous study, we found that the levels of FasL and Il5Ra of the untreated TB cases were lower when we compared it to that of community controls (data not shown) . These results correlate with the phenotypic results which indicates that there is an increase in the surface expression of FASL and IL5RA during treatment, even though those changes are not statistically significant.…”
Section: Discussionsupporting
confidence: 59%
“…Recently IL5RA was found to be under-expressed in human tuberculosis (TB) patients compared with healthy controls [33]. Further, after 2 and 6 months of treatment for TB, IL5RA was found overexpressed in the treated patient group compared to the healthy controls, indicating a reactivation of the immune cells [33]. This is in line with the present study, where this gene is significantly under-expressed in the para-tuberculosis infected and exposed samples compared with controls.…”
Section: Discussionsupporting
confidence: 90%
“…IL5 is a cytokine that acts as a growth and differentiation factor for both B cells and eosinophils. Recently IL5RA was found to be under-expressed in human tuberculosis (TB) patients compared with healthy controls [33]. Further, after 2 and 6 months of treatment for TB, IL5RA was found overexpressed in the treated patient group compared to the healthy controls, indicating a reactivation of the immune cells [33].…”
Section: Discussionmentioning
confidence: 99%
“…Those authors also reported increased BAFF expression levels in pleural effusions of M. tuberculosis-infected patients with pleurisy. In another study, APRIL expression was shown to be increased in B cells of M. tuberculosis-infected patients after 6 months of anti-M. tuberculosis treatment (140). Finally, a recent study confirmed the BAFF-and APRIL-inducing effect of M. tuberculosis by measuring serum BAFF and APRIL levels in patients with latent M. tuberculosis infection (141).…”
Section: Bacteria Bacterial Infections Of the Respiratory Systemmentioning
confidence: 89%